Effect of soymilk coagulating pH on tofu qualities - Duc, Nguyen Quang; Que, Nguyen Thi; Doan, Nguyen Duc; Nguyen, Phuong Xuan; Hong Nga, Luong (Vietnam Journal of Science and Technology, 2021)
Tofu is a common food in Vietnamese and global cuisine. It has high nutritional value, good flavor and texture that it is easy to produce other food from it. In Hanoi, Mo tofu is a traditional product that produced from tofu- whey, which is commonly produced by small scale producers. In this research, effect of coagulating pH on the formation of some linkages and tofu texture and qualities. The results showed that pH effected on S-S linkage and Ho index or phobicity on Mo tofu. At pH=5.8, Mo tofu had the highest moisture of 83.71%, highest water holding capacity of 8.96g/g protein, low hardness, rather high elasticity